2017
DOI: 10.1038/ng.3859
|View full text |Cite
|
Sign up to set email alerts
|

Widespread adenine N6-methylation of active genes in fungi

Abstract: N6-methyldeoxyadenine (6mA) is a noncanonical DNA base modification present at low levels in plant and animal genomes 1-4 , but its prevalence and association with genome function in other eukaryotic lineages remains poorly understood. Here we report that abundant 6mA is associated with transcriptionally active genes in early-diverging fungal lineages 5 . Using single-molecule long-read sequencing of 16 diverse fungal genomes, we observed that up to 2.8% of all adenines were methylated in early-diverging fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
294
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(320 citation statements)
references
References 51 publications
15
294
1
1
Order By: Relevance
“…Twenty-eight 4mC (0.13%) and 10 6mA (0.017%) modification sites were identified in the O. sinensis mt genome ( Figure 1 and Table 6 ). The 6mA levels were lower than previously reported for nucleotide methylation (0.048–0.21%) in eukaryotic nuclear genomes (Mondo et al, 2017). Most 6mA and 4mC were distributed in intergenic regions (between tRNA and nad4L / nad6/cox2 , or between tRNA and tRNA) or in intron regions of different genes (e.g., nad1 - 2, cox1 - 2, cob, rnl ), with only three located in the genes.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Twenty-eight 4mC (0.13%) and 10 6mA (0.017%) modification sites were identified in the O. sinensis mt genome ( Figure 1 and Table 6 ). The 6mA levels were lower than previously reported for nucleotide methylation (0.048–0.21%) in eukaryotic nuclear genomes (Mondo et al, 2017). Most 6mA and 4mC were distributed in intergenic regions (between tRNA and nad4L / nad6/cox2 , or between tRNA and tRNA) or in intron regions of different genes (e.g., nad1 - 2, cox1 - 2, cob, rnl ), with only three located in the genes.…”
Section: Resultscontrasting
confidence: 79%
“…Bisulfite sequencing has enabled genome-wide surveys of 5mC methylation (Masser et al, 2016), a well-established epigenomic mark in eukaryotes, but the historic absence of tools for studying 6mA and 4mC modifications has precluded more comprehensive studies of 6mA and 4mC methylation. Recently, Mondo et al (2017) firstly analyzed 6mA in fungi by SMRT, and revealed its role as a gene-expression-associated epigenomic mark. In this study, SMRT sequencing revealed that not only 6mA but also 4mC were presented in the fungal mt genome.…”
Section: Discussionmentioning
confidence: 99%
“…Genes for the enzymes that modify DNA or histones are also largely conserved [14, 18, 26]. One recent major discovery is the rather widespread distribution of 6-methyladenine observed in the basal lineages that is apparently absent from the Dikarya [30]. Similarly, the Sacharomycetaceae can no longer methylate cytosines or adenines in DNA or methylate lysines of histone H3 at positions 9 and 27 (Figure 1).…”
Section: Chromatin: An Assembly Of Dna Proteins and Rnamentioning
confidence: 99%
“…24 Another naturally occurring DNA modification, N 6 -methyladenine ( N 6 -mA or 6mA) (Figure 1a), was previously thought to be absent in metazoans and only present in prokaryotes and a limited number of unicellular eukaryotes. 5,6 Recently, several new reports described the genomic distributions of N 6 -mA in many phylogenetically distinct eukaryotes including fungi, 7 green algae, 8 insects, 9 nematodes, 10 frogs, 11 fish, 12 and mammals. 1113 Interestingly, the genomic abundance of N 6 -mA varies from ~0.0001–0.0003% of adenines in plants and mammals to as high as 2.8% of adenines in early diverging fungi.…”
Section: Introductionmentioning
confidence: 99%